Sistem Pendukung Keputusan Pemilihan Biji Kopi Arabika Terbaik Menggunakan Metode SMART - Supiyandi Supiyandi; Chairul Rizal; Muhammad Noor Hasan Siregar; Eka Putra; Rusmin Saragih (Building of Informatics, Technology and Science (BITS), 2022)
Arabica coffee beans are one of the main varieties of coffee beans developed in Indonesia. In making decisions to determine quality Arabica coffee beans, an appropriate system is needed to analyze problems in solving and efficient and accurate data presentation. Therefore, a computer-based system or method is needed to facilitate the selection of the best Arabica coffee beans. This study uses the Simple Multi Attribute Rating Technique (SMART) method. The SMART method is a decision-making method to solve the problem of choosing a multi-objective choice among several criteria, so that later it will be able to produce an effective and efficient analysis. The input criteria that are the priority in selecting the best Arabica coffee beans are aroma with a weight of 25, color with a weight of 25, taste with a weight of 25, dirt content with a weight of 15, and price with a weight of 10. Of the 25 alternatives tested in this system, Gayo Avatara Natural Arabica coffee beans were the best first alternative, followed by Aceh Gayo Wet Hull, Java Ijen Natural, Java Ijen Honey, and Kintamani Natural. This decision support system for selecting the best Arabica coffee beans provides speed, accuracy, and data accuracy in selecting the best Arabica coffee beans which will be used by coffee lovers to provide coffee with a delicious taste. So the results of the decision from 25 types of Arabica coffee, there are 11 types of Arabica coffee with a rating of "Very Good", 10 types of Arabica coffee with a rating of "Good", and 4 types of Arabica coffee with a rating of "Quite Good".